POSTER HAK ASASI ANAK - Prayanto Widyo Harsanto (SURYA SENI, 2007)
Talking about children world is always fun because there is innocence, cheerfulness, honesty, and a lot of hope. Since the future of our nation and country is on their shoulders.  But, in everyday life, a lot of children cannot enjoy the  beautiful “Garden of Eden”. Not only few children that are in fact ﬂ ung away in  the “sick world”. They have to live their days with pains, have no hope, and their rights are taken by force.On television and other various media, we can almost see and read everyday that children become violent victim in family (KDRT). The violent criminal can be the closest ones (father, mother, older brother/sister, uncle, aunty), and canbe also foreign people (in kidnapping case, children exploitation). The Law of Children’s Rights Protection seems to be powerless. The clauses that threaten the criminals do not make them frighten or deterred. Not all children of courseundergo bad experiences. There are still a lot of children who can grow and develop in conducive environment. They feel love as they should have and their basic rights are fulﬁ lled.By taking the subject of children world, and in purpose taking pictures of children world from two different sides as mentioned above, the aim of  designing this poster is to remind, make society realize, especially them who care of children,to see the reality around us. In fact, there are a lot of children who need our hands, attention, and deserve our ﬁghtagainst some factors that take their rights by force.Through poster media with photographic approach, we can show the reality that will easily be understood by society. It is real photos that show the real condition so that they can convince and awaken those who see the photos.Keywords: Poster, Children’s  right, and Photography